Trends of Students of the Department of Sociology Towards the Difficulties of Choosing a University Specialty (Students Of The Fourth Year in The Department Of Sociology As a Model) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Choosing the university Specialty is one of the most important decisions that a student must take at the beginning of his university life, and the student faces a range of difficulties that may affect the process of choosing the profession of the future. This research deals with some of the factors that may affect the student's choice of university Specialty. The extent of these factors will be determined by selecting the following hypotheses: - There is a statistically significant relationship between parents' pressure, and the inability of the student to choose the right university Specialty. - There is a statistically significant relationship between the low economic level of the family and the inability of the student to choose freely. - There is a statistically significant relationship between the student’s age and his inability to choose the university Specialty that suits him. - There is a statistically significant relationship between the intervention of friends and the inability to choose the appropriate Specialty. - There is a statistically significant relationship between the freedom to choose university major and academic excellence. The researcher designed a questionnaire that was applied to a sample of fifty students from the fourth – year students of the Department of Sociology at Tishreen University. The results of the research show the following: The weakness of the role of the family such as the parents pressure, economic aspect in the university major selecting process. I also shows the weakness of the role of peers in the selection process, and it became clear that the young age of the student greatly affects the process of selection of his Specialty, but that success and excellence is not limited to those who choose their own specialty, A person may succeed and make his life a success story as long as he has the will to do so